STUDENTS’ READINESS IN USING MOOC FOR TEACHING AND LEARNING - Zulkifli, Norfarahi Zulkifli; Mohamed Maidin, Fathilah Begum; Abd Halim, Adilah Hafizah; Ali, Ummul Hafizah; Ahmad Kuthi, Hajaratul Adhwa' (RedWhite Press, 2019)
Malaysia Education Blueprint 2015-2025 (Higher Education) emphasizes on the usage of information technology and transformation in teaching and learning process. The 9th shift from the blueprint; globalised online learning is to transform the education system and uses information technologies to enhance the learning quality in Malaysia. This suits the Education 4.0 where 21st century skills are important to be applied in education. Massive Open Online Courses (MOOC) is one platform that has been introduced as a new approach in teaching and learning process. This quantitative study aims to look at students? readiness in using MOOC in their teaching and learning process. To serve this purpose, a questionnaire was administered to 213 students at one polytechnic in the Southern Zone. Data were measured using Likert Scale of 1-5 and analysed using Statistical Package for Social Science (SPSS). Descriptive statistics using mean were reported to describe the students? readiness. The findings show that the level of readiness for students to use MOOC is in the highest level with the overall mean of 4.0238. Results express that students are ready to use MOOC in their teaching and learning.